1908 La. Acts 405-06 - (:unkn) unknown (My University, 1908)
An Act to Protect Game Birds. . . ,§ 7: That it shall be unlawful to kill any of the birds named in this Act in the open season, noted herein by any means other than by ordinary gun capable of being held to and shot from the shoulder.
Keywords: HUNTING REGULATION